The Warming of the Chukchi Slope Through the Barrow Canyon Outflow in the 2016–2017 Winter. Issue 11 (11th November 2019) - Kimura, Satoshi; Onodera, Jonaotaro; Itoh, Motoyo; Kikuchi, Takashi; Nishino, Shigeto; Kawaguchi, Yusuke; Watanabe, Eiji; Harada, Naomi
Abstract: The shallow Chukchi Sea is a gateway to the Arctic Ocean for Pacific‐origin waters. While a substantial portion of the Pacific‐origin waters flows through Barrow Canyon in the northeast corner of the Chukchi Sea, little is known on the hydrography of the surrounding regions in winter. We present profiles of wintertime hydrography on the Chukchi slope from an autonomous profiling instrument and mooring records in Barrow Canyon. The central and western sectors of Barrow Canyon in December 2016 to February 2017 were anomalously warm (∼0.5 °C warmer than the climatology) with the flow orienting toward the Arctic Ocean. Unlike the summertime warming near the surface, the warm outflow has a temperature maximum at 80 dbar, and this outflow modifies the water mass properties on the Chukchi slope 70 km north of the canyon. Based on our Barrow Canyon mooring records starting in 2002, this is the first time that such warming is recorded on the outflow in winter. We discuss that this is due to the combination of the Barrow Canyon outflow favorable wind pattern and warming in the southern Chukchi Sea (the Gulf of Alaska and the Bering Sea) before the winter. Key Points: The Barrow Canyon outflow was anomalously warm in the winter 2016–2017, and the warming reached below 100 dbar on the Chukchi slope The wind was the outflow favorable in the winter 2016–2017, and the south of the Chukchi was warm before the outflow The sustained winds and the ocean south of the Chukchi Sea favor the warm Barrow Canyon outflow for the first time in our record